Given: (x^2 + 2ax + 1)^(1/2)

is it correct to say that x^2 + 2ax + 1 = (x + a)^2 (and make the assumption that a^2 = 1) such that

(x^2 + 2ax + 1)^(1/2) = |(x + a)| ?

Printable View

- Apr 7th 2010, 10:29 AMNoxide[SOLVED] Quadratic expression
Given: (x^2 + 2ax + 1)^(1/2)

is it correct to say that x^2 + 2ax + 1 = (x + a)^2 (and make the assumption that a^2 = 1) such that

(x^2 + 2ax + 1)^(1/2) = |(x + a)| ? - Apr 7th 2010, 10:32 AMAmer
x^2 + 2ax + 1 = (x + a)^2

this is not correct for $\displaystyle a\ne 1 $

$\displaystyle (x+a)^2 = x^2 +2ax +a^2 $